2017
DOI: 10.1038/s41598-017-02287-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of 1,5-anhydroglucitol identifies novel genetic loci linked to glucose metabolism

Abstract: 1,5-anhydroglucitol (1,5-AG) is a biomarker of hyperglycemic excursions associated with diabetic complications. Because of its structural similarity to glucose, genetic studies of 1,5-AG can deliver complementary insights into glucose metabolism. We conducted genome-wide association studies of serum 1,5-AG concentrations in 7,550 European ancestry (EA) and 2,030 African American participants (AA) free of diagnosed diabetes from the ARIC Study. Seven loci in/near EFNA1/SLC50A1, MCM6/LCT, SI, MGAM, MGAM2, SLC5A1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Among the 6 top regulated genes in SRNS: ALDOB (aldolase B), is specifically bound to FBPase in the kidney, and participates in the gluconeogenic pathway [19]. MGAM encodes maltase-glucoamylase, which is an intestinal brush border membrane enzyme involved in carbohydrate digestion [20]. MGAM expresses in the kidney, an important target enzyme for the treatment of type-2 diabetes and also takes part in energy supply [21].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 6 top regulated genes in SRNS: ALDOB (aldolase B), is specifically bound to FBPase in the kidney, and participates in the gluconeogenic pathway [19]. MGAM encodes maltase-glucoamylase, which is an intestinal brush border membrane enzyme involved in carbohydrate digestion [20]. MGAM expresses in the kidney, an important target enzyme for the treatment of type-2 diabetes and also takes part in energy supply [21].…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 9,083 individuals of European ancestry with genotypes and QT interval at baseline. The genotyping of these samples on the Affymetrix genome-wide Human SNP Array 6.0, quality control, and imputation to the 1000 Genomes Phase I Integrated Release Version 3 haplotype panel are described elsewhere [69, 70]. We converted IMPUTE2 genotype probabilities to PLINK ‘hard’ calls, setting genotypes with uncertainty greater than 0.25 to missing, and retaining variants with < 10% missing data, a Hardy Weinberg equilibrium test p < 1×10 -6 , and imputation quality score ≥ 0.3, (as for the GERA study).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, studies of the renal reabsorption of fructose in rat proximal tubules revealed that this process can be blocked to a large extent by phlorizin and that it is Na +dependent [54]. In addition, recent genome-wide association studies revealed that genetic variations of SGLT5 are associated with impaired 1,5-anhydroglucitol (1,5-AG) blood levels [96]. 1,5-AG is a monosaccharide found in nearly all foods and its blood concentration decreases during times of hyperglycemia and, within a couple of weeks, returns to normal levels in the absence of hyperglycemia.…”
Section: Slc5a10/sglt5mentioning
confidence: 99%